Penentu Kinerja Keuangan Perusahaan Manufaktur di Indonesia Dengan GCG Sebagai Moderasi - Agda Laily Ahadiya (AKUNTANSI 45, 2025)
This study aimed to analyze the effect of environmental performance, postemployment benefits, and leverage on financial performance moderated by GCG in consumer goods manufacturing companies. The independent variables in this study used environmental performance as measured by PROPERS’s score, postemployment benefits as measured by comparison of the post-employment benefits payable to overall debt, and leverage as measured by two indicators, that are Debt to Total Assets Ratio (DAR) and Debt to Total Equity Ratio (DER). For the dependent variable, financial performance are measured using the Return on Assets (ROA) and Return on Equity (ROE) indicators. GCG as moderating variable is measured by the number of commissioners. The population of this study is consumer goods sub-sector manufacturing companies which listed on IDX adnd as PROPER participants in 2018-2020. Data were collected by using purposive sampling, so there are 73 observations data were processed using SEM PLS analysis. The result of this study show that environmental performance has a positive and significant effect on financial performance. Post-employment benefits has a negative and significant effect on financial performance. Leverage has a negative and significant performance and GCG doesn’t moderate the relationship between leverage and financial performance.